Design Micro Hydro Power Plant for Generate Electrical Energy About 3000 to 5000 Watt - Suryatna, Bambang Sugeng (Universitas Negeri Semarang, 2020)
The aim of the reseach is making the prototype design of waterwheel-based Microhydro Power Plant (MHPP). The findings of this study are the Prototype Model of Micro Hydro Power Plant (MHPP) for generate electrical energy with power 3000 to 5000 watt. This model has been constructed of fout components, sucs are (1) the disain of waterwheel prototype, (2) the disain of converter speed water wheel to dynamo, (3) the water chanel for input Potential Energy, and (4) Conductor Network of MHPP to homes.